Regulation of Gram-Positive Conjugation - Verena Kohler; Walter Keller; Elisabeth Grohmann (Frontiers in Microbiology, 2019)
Type IV Secretion Systems (T4SSs) are membrane-spanning multiprotein complexes dedicated to protein secretion or conjugative DNA transport (conjugation systems) in bacteria. The prototype and best-characterized T4SS is that of the Gram-negative soil bacterium Agrobacterium tumefaciens. For Gram-positive bacteria, only conjugative T4SSs have been characterized in some biochemical, structural, and mechanistic details. These conjugation systems are predominantly encoded by self-transmissible plasmids but are also increasingly detected on integrative and conjugative elements (ICEs) and transposons. Here, we report regulatory details of conjugation systems from Enterococcus model plasmids pIP501 and pCF10, Bacillus plasmid pLS1, Clostridium plasmid pCW3, and staphylococcal plasmid pSK41. In addition, regulation of conjugative processes of ICEs (ICEBs1, ICESt1, ICESt3) by master regulators belonging to diverse repressor families will be discussed. A special focus of this review lies on the comparison of regulatory mechanisms executed by proteins belonging to the RRNPP family. These regulators share a common fold and govern several essential bacterial processes, including conjugative transfer.